Tingkat Aspirasi Karir Siswa di Tinjau dari Jenis Kelamin, Jurusan dan Daerah Tempat Tinggal - Afriyadi Sofyan; A Muri Yusuf; Daharnis Daharnis (Jurnal Konseling dan Pendidikan, 2013)
The career aspirations level is one heavily influenced by various factors, such as sex, major of study and placeof residence. Of course, associated with the service of career guidance, need to be obtained a clear picture of conditions career aspirations of students with a variety of factors that can be influenced. This research uses a quantitative approach to type descriptive comparative. The research methods applied in the study was ex post facto with a sampling of data retrieval, research design using factorial design 2 x 2 x 2. Data analysis results showed that:The level of studentscareer aspirations in terms of sex, major ofstudyand placeof residenceare in high category. There are difference’s between the levels of student career aspiration in terms of sex, major ofstudy and place ofresidence.In general, there is no interaction between the variables gender, major ofstudy and place of residence in determining the level of students career aspirations.